Human-centered artificial intelligence: Creating a better customer experience In the banking sector - OBUCHETTIAR, Arul Krishnaraj (Institutional Knowledge at Singapore Management University, 2022)
Changes in technology have shaped how corporate and retail businesses have evolved, and customers’ preferences have rapidly changed along with them. The advent of smart digital devices and social media has shaped how consumers interact and transact with their financial institutions over the past two decades. However, this transformation has just begun. With the rapid evolution of new technologies and customers' growing preference for digital engagement with financial institutions, organizations need to adapt and align with emerging technologies that support speed, accuracy, efficiency, and security in a user-friendly manner. Today, consumers want hyper-personalized interactions that are more frequent and proactive. Moreover, there is a growing need for financial institutions to cater to consumers' new demands. Financial institutions, such as banks, continuously adapt to the latest technologies and keep pace with evolving customer behaviors, needs, and experiences. One such emerging technology is artificial intelligence (AI). Many organizations realize the potential of AI, and they are keen to use its advantages with a human touch. However, a human-centered AI system must be capable of understanding human characteristics and making decisions that are similar to humans. This study aims to help banks to understand the importance of processing customer emotions and minds from the unstructured data captured from various Omni channels in order to develop full-fledged human-centered AI-enabled products and services with AI transparency by practicing a co-development mindset between the key stakeholders (Banks, IT vendors, and Focus Groups). This paper discusses a theoretical model to study the effects of human-centered AI and a framework developed to help financial institutions adapt and build effective AI-enabled products and services with a human touch for a better customer experience and assist in staying competent during their digital transformation journeys.